Silver electrodeposition for multipactor mitigation - Belfio, Julie; Belhaj, Mohamed; Lazar, Florica; Jbara, Omar (International Workshop on Multipactor, Corona and Passive Intermodulation (MULCOPIM 2022), 2022)
The multipactor effect is an electron avalanche like phenomenon that can occur in microwave components under vacuum. This undesirable effect results from the synchronism between the Radiofrequency-wave and the electron emission phenomenon of microwave-components materials that may lead to an exponential increase of the electron density [1]. The new trend in the space telecommunication is to increase the RF power density that leads to an increased multipactor risk. To circumscribe this risk, an interesting strategy consists to produce rough surfaces at microscopic scale with low Total Electron Emission Yield (TEEY) [2]. For this purpose, many technics are used such as laser ablation [3], micro-porous by photolithography [4], copper nanowires [5] or micro-structured gold/silver coatings [6], etc. For monolithic components produced by 3D printing, a major part of these nowadays used solutions are difficult to apply or inapplicable. That why, in this work, we explore the capabilities of electrodeposition techniques to produce low TEEY surfaces. This technique (fluid) could be suitable 3D printed components in particular. In this work, surface roughness was induced directly during the silver electrochemical deposition on nickel substrate at ambient temperature with a bath composition that responds to some green chemistry aspect as the suppression of toxic product as cyanide (REACH). This paper was divided in two parts. In the first part, we describe the effect of bath compositions and electrodeposition parameters on the surface morphology. In the second part, we present the effect of these surfaces on the TEEY. We will show that some produced morphologies lead to a substantial overall decrease of the TEEY. A scanning electron microscopy with electron dispersive X-Ray analysis were used to link the TEEY to surface morphology and chemical composition.
Keywords: ELECTRODEPOSITION; MITIGATION; MULTIPACTOR